Taunton's complete illustrated guide to using woodworking tools - Bird, Lonnie; Taunton Press (Newtown, CT : Taunton Press, 2004)
In this step-by-step pictorial reference, Bird, a long-time contributing editor to American Woodworker, explains how to use all the tools found in a modern woodworking shop, and offers advice on choosing the right tools for the job, setting up a shop, and basic and special operations.
Wood and the Shop -- Working with wood -- Outfitting the shop -- Benches, Clamps, and Assembly -- Benches and clamps -- Gluing and assembly -- Hand Tools -- Measuring and marking tools -- Handsaws and chisels -- Planes and planing -- Files and rasps -- Sharpening hand tools -- Power Tools -- The table saw -- The jointer and planer -- The bandsaw -- The shaper -- The router table -- Drilling and mortising tools.
Includes bibliographical references (p. 274) and index.
Keywords: Woodworking tools